Productive economic education of Indonesian Minang Migrants' children: A phenomenological study - Wahyuni, Sri; Wahjoedi, Wahjoedi; Mukhlis, Imam; Rahayu, Wening Patmi (Edelweiss Applied Science and Technology, 2025)
Productive economic education is very important to provide to children to help them become more independent as adults and utilize economic opportunities more effectively. This research was conducted to fill the gap in family economic education literature, especially regarding productive economic education. This research used a qualitative design with a phenomenological approach, involving informants from Minang migrants who have lived for more than four years in Malang Raya, Indonesia, with a total of 28 informants, namely 14 key informants and 14 supporting informants. Semi-structured interviews were conducted directly with informants at shops, informants' homes, and during Minang family activities. This research produced four themes: (1) children's participation in helping parents' businesses, (2) involving children in household chores, (3) parental constraints in children's productive economic activities, and (4) forms of productive economic intensity given to children. The findings showed that parents have included children in productive economic activities; children are also involved in family businesses and household activities. In instilling productive economic activities in children, there are many obstacles faced by parents, and the intensity of productive economic education that is more dominantly given by parents to children is in the form of exemplary behavior. The results of this study indicate the existence of a family-based productive economic education model through child participation, and the findings can provide a new perspective on economic education based on direct practice in the family environment.